Studentification in Area Around the Private University Cluster in Bendan, Semarang - Silvia Tria Septiani; Retno Susanti (Teknik PWK (Perencanaan Wilayah Kota), 2023)
Studentification can be understood as a process caused by the concentration of students in an area accompanied by changes in the physical, economic, social, and cultural aspects of the area around the university. However, along with its development, the Bendan Private Higher Education Area was influenced by physical conditions and policies regarding development restrictions. The purpose of this study was to find changes that occurred in the area around Bendan Private College in four dimensions of studentification; physical, economic, social, and cultural aspects due to the studentification process. The studentification process research approach used is deductive. The method used in this study is a qualitative method to provide an in-depth explanation of the studentification process that occurs in the Bendan College Area. Semi-structured interviews were conducted with relevant stakeholders; Urban Village Officer, LPMK, and community leaders. It showed that the presence of universities and students resulted in developments in the area with changes in land cover, supporting infrastructure for students, changes in building functions, the emergence of student accommodation, changes in environmental conditions, changes in livelihoods, economic improvements, increases in land prices, an increase in the young population, student lifestyles, cultural assimilation, and displacement.